The struggle of Hungarian Lutherans under communism - Baer, H. David (Helmut David), 1968- (Eugenia and Hugh M. Stewart '26 series on Eastern Europe., 2006)
What does a religious community do when confronted by a political regime determined to eliminate religion? Under communism, Hungary's persecuted Lutheran Church tried desperately to find a strategy for survival while remaining faithful to its Christian beliefs. Appealing to the Lutheran Confessions, many argued that the church can do whatever is necessary to survive provided it does not compromise on its essential ministry, while others, appealing to the witness of the confessor Bishop Lajos Ordass, argued that the church must uncompromisingly witness to the truth even if that means ecclesiological extinction. Here, H. David Baer draws upon the disciplines of theology, history, ethics, and politics to provide a comprehensive analysis of the different strategies developed by the church to preserve its integrity. Relying on previously unnoted archival documents and other primary sources, Baer's telling of the history is also a sensitive and moving account of courage and cowardice in the face of religious persecution. This book should be of interest not only to students of religion in Eastern Europe but also to anyone concerned about the problems that arise wherever there is religious persecution.